2021
DOI: 10.1038/s41598-021-91929-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring physicochemical and cytogenomic diversity of African cowpea and common bean

Abstract: In sub-Saharan Africa, grain legumes (pulses) are essential food sources and play an important role in sustainable agriculture. Among the major pulse crops, the native cowpea (Vigna unguiculata) and introduced common bean (Phaseolus vulgaris) stand out. This paper has two main goals. First, we provide a comprehensive view of the available genetic resources of these genera in Africa, including data on germplasm collections and mapping biodiversity-rich areas. Second, we investigate patterns of physicochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Our study shows that Phaseolus and Vigna species can be distinguished from each other, namely in terms of proximate composition (see Figures 3 and 4). In line with our findings, a recent study conducted by Catarino et al [58], using cluster analysis, showed a clear difference between Phaseolus and Vigna species in terms of mineral composition. Nevertheless, the protein content is quite uniform among the studied Phaseolus and Vigna species, but the samples from these two species collected in Maputo markets (i.e., MP5 Pv and MP6 Vr) revealed the highest protein content.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that Phaseolus and Vigna species can be distinguished from each other, namely in terms of proximate composition (see Figures 3 and 4). In line with our findings, a recent study conducted by Catarino et al [58], using cluster analysis, showed a clear difference between Phaseolus and Vigna species in terms of mineral composition. Nevertheless, the protein content is quite uniform among the studied Phaseolus and Vigna species, but the samples from these two species collected in Maputo markets (i.e., MP5 Pv and MP6 Vr) revealed the highest protein content.…”
Section: Discussionsupporting
confidence: 93%
“…Over the last decades, a large amount of work was done on the importance of nutritional and medicinal uses of African plants (Addis et al, 2013;Catarino et al, 2016Catarino et al, , 2021a. These plants already contribute to food security of local populations, are often harvested and traded in town markets, and some are also used in traditional medicine (Shackleton et al, 2007(Shackleton et al, , 2009Cernansky, 2015;Charrua et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of 11 minerals (boron—B, calcium—Ca, copper—Cu, iron—Fe, potassium—K, magnesium—Mg, manganese—Mn, sodium—Na, phosphorous—P, sulphur—S, zinc—Zn) in seeds of Cajanus cajan , Phaseolus lunatus , Phaseolus vulgaris , Vigna angularis , Vigna radiata , and Vigna unguiculata were determined by inductively coupled plasma optical emission spectrometry (Thermo Scientific iCAP 7000 Plus Series ICP-OES spectrometer, Thermo Fisher Scientific, Waltham, MA, USA) after digestion in aqua regia (a mixture of nitric acid and hydrochloric acid (1:3)) at 105 °C during 60 min [ 23 , 37 ]. Calibration was made using the controls prepared with the same analytical procedure and reagents but without sample.…”
Section: Methodsmentioning
confidence: 99%
“…Vigna unguiculata and Phaseolus vulgaris , the main pulse crops on the African continent, are essential sources of minerals and vitamins [ 21 , 22 ]. According to Catarino et al [ 23 ], Vigna unguiculata has a higher content of boron, magnesium, sulphur, and zinc, while P. vulgaris has more iron, calcium, and copper. Zinc and iron deficiencies have the worst impact on public health, but other minerals, such as calcium and magnesium, are also vital to human health [ 24 ].…”
Section: Introductionmentioning
confidence: 99%